Investigation of Seroprevalence of Hepatitis B, Hepatitis C and HIV in Hemodialysis Patients - Duygu Fındık (Journal of Contemporary Medicine, 2021)
Aim: Impairments in the immune system of patients undergoing HD cause patients to be more sensitive to infection agents. The purpose of this study; to determine the seroprevalance of HBV, HCV and HIV in patients undergoing hemodialysis treatment. Materials and Methods: HBsAg, Anti-HBs, Anti-HBc IgM, Anti-HBc IgG, HBV-DNA, Anti-HCV, HCV-RNA and Anti-HIV parameters studied from serum samples of Chronic Kidney Patients (CKD) undergoing hemodialysis treatment at Selçuk University Faculty of Medicine It has been scanned retrospectively for ten years. Results: HBsAg was determined in 17 (0.40%) of 4155 hemodialysis patients and Anti-HBs was positive in 454 (11.2%). Anti-HCV was detected as positive in 14 (0.33%) serum. HBV-DNA was found to be positive in 13 (76.5%) of HBsAg positive HD patients and in 12 (85.7%) of Anti-HCV positive patients. Anti-HIV antibodies were not detected in any of the serum samples. Conclusions: The results of our study have shown that proper infection control measures in hemodialysis patients can reduce the contamination of infectious agents. In addition, factors such as vaccination scheme, inoculation site and dose should be selected appropriately, taking into account the immunosuppressive state of the patients.